Public administration ethics: Theory and praxis in the United States of America - Cooper, Terry L.
Administrative ethics has been a subject of werious scholarship in the United States for approximately fifteen years. During this period there has been a rapid expansion in the literature. Here the growing recognition of the extent to which public administrators exercise discretion in shapping public policy, as well as in day-to-day decision-makeup, led to greater concern for the values and principles which inform their judgement. Whatever the reason may be, the literature on pulbic administration ethics has mushroomed during the last decade and a half. In this context the long-term value of cultivating wise judgement, which requires theoretical, conceptual, abstract thinking, but links it to practice through c
Keywords: Public Administration; Ethics; Public Administration - U.S.A.